PABLO DE MENDÍBIL (1788-1832), ESPÍA DE FERNANDO VII - Joaquín Álvarez Barrientos (Cuadernos de Ilustración y Romanticismo)
Several testimonies documenting the activity of Pablo de Mendíbil as a spy for the monarchy of Fernando VII in London are provided. First I place the life and work of the author.